A novel concept of Vertical Up-Flow Forward Osmosis reactor: Design, performance and evaluation. (October 2021) - Patel, Asfak; Mungray, Arvind Kumar; Mungray, Alka
Abstract: Performance of the forward osmosis (FO) process is limited due to the decline in water flux and increase in reverse salt flux. In this study, a novel Vertical Up-Flow Forward Osmosis (VUF-FO) reactor was designed and evaluated for eight different contacting patterns of feed and draw agent (DA). The best contacting pattern was compared with the basic H-shape reactor. Pulsating inlets were used for the recirculation of the feed and DA which helped in improving the performance by reducing the concentration polarization on membrane. Water flux in FO (active layer facing feed side) and PRO (active layer facing draw side) mode was 12.75 and 16.28 L/m 2 hr (LMH) respectively for the contacting pattern R3 and R5 after 8 h of the process. While the water flux in the H-shape reactor was 9.12 and 12.54 LMH for FO and PRO mode respectively. Diffusional behavior of water flux and reverse salt flux were also evaluated for both the FO reactors. Water flux in the H-shape reactor was declined to more than 60% from its initial value in both the modes (i.e. FO and PRO) due to the concentration polarization on membrane. Only 10% decline in water flux was observed for the VUF-FO reactor. This showed a better consistency of water flux in the VUF-FO reactor. The reverse salt flux in the VUF-FO reactor was less than 85% compared to the H-shape reactor. Therefore, a novel designed reactor improved the overall performance of FO in terms of water flux and reverse salt flux. Graphical abstract: Image 1 Highlights: A novel Vertical Up-Flow Forward Osmosis (VUF-FO) reactor was designed. The performance of VUF-FO reactor was compared with the basic H-shape reactor. Effect of boundary layers on the performance of the reactors was discussed. Water flux and RSF were improved in VUF-FO reactor compared to H-shape reactor. RSF was high in H-shape reactor while it was low in the VUF-FO reactor.